Between the Lines: A Critical Discourse Analysis of Disability Policy in Portugal - Paula Campos Pinto (Disability Studies Quarterly, 2011)
Law and policy around disability in Portugal, as elsewhere, are undergoing rapid change towards a model based on human rights for all. Whether this transformation translates into real gains for people with disabilities, however, is yet to be proved. This paper addresses this question by undertaking a critical discourse analysis (CDA) of the single most important policy instrument in the disability arena in Portugal: the First National Action Plan for the Integration of People with Disabilities and Impairment (PAIPDI). The analysis demonstrates that while presented under a somehow different package—one in which a new discourse on rights is highlighted—there is much continuity in how the problem of disability is represented and managed in the Portuguese society. However, the adoption of the rights discourse on disability also signals an important shift, one that reflects the increased hegemony of the disability movement, not just nationally but globally. In this sense, new and exciting possibilities for disabled people are opening up to reshape the power relations that in the past have sustained their domination. Its potential, however, will greatly depend on the ability of the disability movement to build on this momentum and use human rights as a tool to push for disability justice in social, and not just discursive, practices.
Keywords: Critical discourse analysis; disability policy; human rights; Portugal; women with disabilities